The Political Economy of Global Agriculture: Effects on Agriculture, Farmers, Consumers and Economic Growth - Dastagiri, M.B.; Vajrala, Anjani Sneha (European Scientific Journal, ESJ, 2018)
International political economy deals with mutual interaction of international politics and international economics. The ever-changing political scenarios, be it right-wing or left-wing, agriculture in particular has been neglected. The main focus of the paper is to study the effects of political economy on agriculture, farmers, consumer welfare and economic growth. The data on indicators collected from FAO,World Bank, IMF, UNDES, WEF, OECD, CGIAR reports. The growth rates, Agricultural Orientation Index (AOI) and statistical-analysis estimated. Globally, political and economic systems, international governments like World Bank, IMF and WTO’s attitude towards agriculture is poor. Agriculture must be brought on global political agenda for sustainable food security, economic growth and development and to achieve Millennium Development Goals (MDG’s). The protection of producers and consumers is being based on political will of governments. The study concludes for developing countries, stimulus package is required for the development of agriculture. The political economy of AOI indicates that the countries which have more than 1 will spend more budget in budget allocation towards agriculture. The study found that, clearly agriculture globally is not on the priority list for the local central governments in allocating their budgets towards agriculture. The study suggests that, economic minded politicians and political minded economists who has knowledge of social, political and economic systems are required in efficient economic system of agriculture.